2023
DOI: 10.3389/fmars.2023.1135417
|View full text |Cite
|
Sign up to set email alerts
|

Nature-based coastal restoration: Development of an early-rearing production protocol of sugar kelp (Saccharina latissima Linnaeus) for bottom planting activities in the Gulf of St-Lawrence (Québec, Canada)

Abstract: Successful bottom planting of indigenous macroalgae Saccharina latissima aimed at coastal restoration purposes require the mass production in controlled conditions of strongly fixed, healthy sporophytes followed by optimal transfer techniques in order to ensure viability and vigor of the young seedlings about to be directly introduced in the coastal environment. Early development of S. latissima submitted to different combinations of substrate type (natural vs artificial brick-shaped substrate), gametophyte sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
0
0
Order By: Relevance
“…One strategy to recover populations is to plant new individuals where it has been lost/decreased, aiming to restore the populations. A few studies aiming to find the best techniques for restoration have been performed on S. latissima (Fredriksen et al 2020;Tsiamis et al 2020;Le François et al 2023). In a trial in Quebec, Canada, the production of S. latissima sporophytes was successful and worked best on artificial substrate and using a binder-based method for spraying gametophytes (Le François et al 2023).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…One strategy to recover populations is to plant new individuals where it has been lost/decreased, aiming to restore the populations. A few studies aiming to find the best techniques for restoration have been performed on S. latissima (Fredriksen et al 2020;Tsiamis et al 2020;Le François et al 2023). In a trial in Quebec, Canada, the production of S. latissima sporophytes was successful and worked best on artificial substrate and using a binder-based method for spraying gametophytes (Le François et al 2023).…”
Section: )mentioning
confidence: 99%
“…A few studies aiming to find the best techniques for restoration have been performed on S. latissima (Fredriksen et al 2020;Tsiamis et al 2020;Le François et al 2023). In a trial in Quebec, Canada, the production of S. latissima sporophytes was successful and worked best on artificial substrate and using a binder-based method for spraying gametophytes (Le François et al 2023). In contrast, a study in Scotland revealed that the abundance of S. latissima and other kelps in an artificial reef was low, and in turn, turf seaweeds were abundant (Tsiamis et al 2020).…”
Section: )mentioning
confidence: 99%